A landscape embroiled: experience of nature through experience of art - Milczarczyk, Paula (Polskie Studia Krajobrazowe, 2019)
The article sets out with the theory of “aesthetics of reality” (created by Maria Gołaszewska) and its related method of transferring artistic structures onto non-artistic reality. The resulting construct, which is dubbed a para-artistic structure, becomes the theoretical basis for the aesthetic experience of nature. The so-called “formalization”—a procedure which consists in inserting nature into artistic frameworks—makes natural phenomena acquire a pretense of artwork. Nature as a picture becomes a landscape, while terms connected with the aesthetics of nature gain artistic qualities, enabling use of such notions as picturesque or kitsch. The methodological proposal by Gołaszewska is subsequently compared with the critical perspective of environmental aesthetics.